'Plain' legal language by courts: mere clarity, an expression of civic friendship or a masquerade of violence?. (2nd January 2022) - van Domselaar, Iris
ABSTRACT: In the Netherlands over the last decade, a range of initiatives have been launched by individual courts, mostly on their own initiative, to make court rulings more comprehensible to average citizens. At the outset, at least from the 'internal point of view' of legal practitioners, it might seem striking that these initiatives predominantly address the comprehensibility of legal language as an exclusively linguistic matter, independent of any jurisprudential stance as to what 'doing law' should consist of in this context. However, this linguistically-oriented approach is far from eccentric: it dovetails nicely with the dominant approach adopted by the plain legal language movement to make the law more comprehensible to citizens. Against the background of a language as activity view, this article analyses and evaluates the use of comprehensible legal language by courts. To do this, an integrative legal–ethical approach is employed, according to which the content and style of court rulings are inextricably linked. More specifically, the Aristotelian concept of civic friendship is introduced as having potential explanatory force for the practice of plain legal language use by Dutch courts. With reference to actual court rulings, it is argued that this concept allows us to conceive of a 'plain' court ruling as a potential expression of a civic-friendly attitude by the judge. In addition, the main dilemmas that civic-friendly judges will be likely to face when writing a comprehensible court ruling are identified. Finally, and on a more critical note, a fundamental concern is raised regarding the practice of plain legal language use by Dutch courts.